The anti-racist organization dismantling systemic racism in the workplace - Daniels, Shereen (Hoboken, NJ John Wiley & sons, Inc., 2022)
"Wait a Minute...Where are all the Black People is an insight into systemic racism baked into business structures, policies and procedures. It's an incite to change. Shereen Daniel's woven personal experience, historical fact, legal proceedings, her HR insight and quantitative analysis into a book that enables business leaders to change their workplace practices through her tried and tested bespoke Models. This essential book will address: How diversity and inclusion initiatives haven't yet solved the problem ; How to use language as a tool to dismantle racism ; How to recognise the problem and analyze for impact ; And how to empower for change The book is brutally honest but gives the knowledge and the tools required to make transformative change and advance racial equity"--
Includes index.
Keywords: Discrimination in employment -- United States; Diversity in the workplace -- United States; Racism in the workplace -- United States; United States -- Race relations